IMPLEMENTASI KEBIJAKAN ELECTRONIC GOVERNMENT DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA MAKASSAR - MULIATI, MULIATI; ASHARIANA, ASHARIANA; ALIF, NUR MUHAMMAD (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
This study aims to analyze the implementation of electronic government (e-government) policies and the factors that influence their implementation at the Population and Civil Registration Office of Makassar City. This study uses a descriptive method with a purposive sampling technique to determine the sample. Primary and secondary data were obtained through observation, interviews, questionnaires, and documentation. Data were analyzed using a quantitative descriptive approach supported by qualitative data. The results of the study indicate that the implementation of e-government at the Population and Civil Registration Office of Makassar City is mostly running very well. The service system obtained an average score of 3.40 (85%), timeliness 3.40 (87.5%), clarity of work mechanisms 3.50 (87.5%), and supporting facilities and infrastructure 3.60 (90%). However, the quality of human resources of the apparatus is still low with a score of 2.70 (67.5%), which is the main obstacle. The factors that influence policy implementation show mixed results. Communication between leaders and subordinates is very good (score 3.40, 85%), and the disposition of leaders in supporting policies is also very good (score 3.40, 87.5%). However, weaknesses were found in the resources of the apparatus and the bureaucratic structure, each with a score of 2.70 (67.5%), which were considered less supportive of the optimal implementation of e-government policies. ABSTRAKPenelitian ini bertujuan untuk menganalisis implementasi kebijakan electronic government (e-government) dan faktor-faktor yang memengaruhi pelaksanaannya di Dinas Kependudukan dan Catatan Sipil Kota Makassar. Penelitian ini menggunakan metode deskriptif dengan teknik purposive sampling untuk menentukan sampel. Data primer dan sekunder diperoleh melalui observasi, wawancara, kuesioner, dan dokumentasi. Data dianalisis menggunakan pendekatan deskriptif kuantitatif yang didukung oleh data kualitatif. Hasil penelitian menunjukkan bahwa implementasi e-government di Dinas Kependudukan dan Catatan Sipil Kota Makassar sebagian besar berjalan sangat baik. Sistem pelayanan memperoleh skor rata-rata 3,40 (85%), ketepatan waktu 3,40 (87,5%), kejelasan mekanisme kerja 3,50 (87,5%), dan sarana serta prasarana pendukung 3,60 (90%). Namun, kualitas sumber daya manusia aparatur masih rendah dengan skor 2,70 (67,5%), yang menjadi hambatan utama. Faktor-faktor yang memengaruhi implementasi kebijakan menunjukkan hasil beragam. Komunikasi antara pimpinan dan bawahan sangat baik (skor 3,40, 85%), dan disposisi pimpinan dalam mendukung kebijakan juga sangat baik (skor 3,40, 87,5%). Namun, kelemahan ditemukan pada sumber daya aparatur dan struktur birokrasi, masing-masing dengan skor 2,70 (67,5%), yang dinilai kurang mendukung implementasi kebijakan e-government secara optimal.